Indian Consensus Guidelines for the Management of Pancreatic Cancer - Lavingia, Viraj; Gohel, Shruti; Shrikhande, Shailesh; Mullapally, Sujith K.; Ramaswamy, Anant; Talwar, Vineet; Saj, Fen; Sood, Tanvi; I., Anu R.; Menon, Munita; Singh, Shalini; Rajappa, Senthil; Seufferlein, Thomas; O'Reilly, Eileen; Sirohi, Bhawna (Indian Journal of Medical and Paediatric Oncology, 2025)
Pancreatic cancer needs a multidisciplinary approach to treatment. These consensus statements encompass all aspects of treatment of pancreatic cancer within the Indian context. This article outlines consensus-based Indian guidelines for pancreatic cancer (PC), created by a national panel of 39 experts using NCCN and ESMO frameworks. Recommendations were systematically developed via evidence review, expert discussion, and conflict-of-interest exclusions. Guidance covers standardized diagnostic workup, risk stratification and multidisciplinary management involving surgical oncology, medical oncology and radiation oncology. Tumor subtypes (resectable, borderline resectable, locally advanced) determine treatment pathways: upfront surgery for eligible patients and neoadjuvant therapy for downstaging, as appropriate. Preferred regimens for advanced/metastatic disease are outlined. Recommendations are tailored to Indian practice, integrating resource stratification and local access issues. Each guideline is graded for evidence strength and consensus level as per ESMO standards. Emphasis on surveillance and early integrated palliative care aims to optimize patient outcomes. These evidence-based guidelines seek to standardize and elevate PC care across diverse settings in India.
Keywords: guideline; medical oncology; pancreatic cancer treatment